2003
DOI: 10.1109/tasc.2003.812410
|View full text |Cite
|
Sign up to set email alerts
|

Field angle dependence of AC losses in stacked Bi-2223 Ag-sheathed tapes

Abstract: In case of applying oxide superconducting tapes to power devices, they are usually stacked face-to-face to form a parallel conductor for the enlargement of current capacity. The accurate estimation of ac losses in the stacked tapes is very important for the basic design of the superconducting devices.In this study, we discuss the angular dependence of the ac losses in the stacked Bi-2223 Ag-sheathed tapes exposed to an external ac magnetic field. First we measure the ac losses in the nontwisted Bi-2223 tapes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…For the 45°case, m versus B is also presented, which was obtained from the measurements as q = m m cos z a , q = B B cos a a (see figure 10). This transformation preserves the area of the loop and consolidates the conclusions that has been done above: in the presence of   B component the loop is similar to the one in 0°applied field, but slightly squeezed (see also [19,20]). For the 90°orientation reliable results could not be obtained in the VSM system due to a weak magnetization of the sample.…”
Section: Orientation Of the Magnetic Fieldsupporting
confidence: 83%
“…For the 45°case, m versus B is also presented, which was obtained from the measurements as q = m m cos z a , q = B B cos a a (see figure 10). This transformation preserves the area of the loop and consolidates the conclusions that has been done above: in the presence of   B component the loop is similar to the one in 0°applied field, but slightly squeezed (see also [19,20]). For the 90°orientation reliable results could not be obtained in the VSM system due to a weak magnetization of the sample.…”
Section: Orientation Of the Magnetic Fieldsupporting
confidence: 83%
“…), respectively. The magnetization losses, W magnetization , per unit volume per AC cycle in stacked BSCCO tapes exposed to the external transverse magnetic fields, B = (B x , B y , 0), with arbitrary angles have been evaluated experimentally using the following relationship [22] W magnetization (B) = − M • dB…”
Section: Specifications Of the Hts Insert For The High Field Magnetmentioning
confidence: 99%
“…The dependence of AC losses in the Bi-2223 Ag-sheathed tapes on the direction of an external applied magnetic field has been observed experimentally [1], [2]. Their results have indicated that the AC losses increase with the field angle with respect to the tape face.…”
Section: Introductionmentioning
confidence: 95%